THE STUDY ON INTERFACIAL BONDING OF EXPANDABLE GRAPHITE BASED INTUMESCENT COATING USING BENTONITE CLAY - KAUR, JESBAINS (2012)

(untitled)
The fast development of science and technology provides us withsophisticated products but concurrently increases the use of combustible materials.The usage of polymeric materials in everyday life increases the risk of fire hazards;therefore flame retardants are often incorporated into them to limit their flammability.This study characterized the interfacial bonding of expandable graphite based intumescent coating on steel substrate with respect to its physical, chemical and mechanical properties after fire test. A range of expandable graphite based intumescent coating formulations were developed with various additives. In these formulations, bentonite clay filler was incorporated to improve the adhesion of coating with substrate. Structural steel substrate was sand blasted and coated with primer coating of zinc phosphate. For mechanical properties, the shear test was conducted according to ASTM 3 163 test procedure and the maximum shear strength was 9.89Mpa for an intumescent coating formulation containing 6% of bentonite clay and 1.32Mpa for formulation without bentonite clay. X-Ray Diffraction 0r)esults s howed boron phosphate,graphite and sassolite were remaining inorganic materials that acted as a thermal barrier or protecting layer at later stages of burning. Formulation containing 6% of bentonite clay had the highest residual weight which was 33.45% and formed a ceramic like protective shield at the char surface thus indicated it has good intumescent effect compared to 25.33% for coating without bentonite clay at 800'c.